Nursing and music: Considerations of Nightingale's environmental philosophy and phenomenology. (16th September 2018) - Parr Vijinski, Jon; Hirst, Sandra P.; Goopy, Suzanne
Abstract: A philosophy of nursing is to express our considered opinion on what we believe to be true about the nature of the profession of nursing and provide a basis for nursing activities. It affirms the ethical values that we hold as fundamental to our practice. For many of us in nursing, our philosophy derives from Nightingale and phenomenology. We believe Nightingale and phenomenology are uniquely placed within nursing philosophies, to assist the nurse to understand the use of music within a holistic, caring‐healing paradigm, as nursing continues to adapt and evolve in the 21st century. This article proposes that both Nightingale's environmental philosophy and phenomenology are excellent intellectual and practice frameworks for nurses to consider music‐based interventions for older adults who experience dementia. The potential outcome is an enhanced understanding of the well‐being of this vulnerable group of older persons.